A ravenous defense: canonical and non-canonical autophagy in immunity. (February 2018) - Sil, Payel; Muse, Ginger; Martinez, Jennifer
Highlights: Pathogens can be targeted by autophagic machinery in a process termed selective autophagy. In xenophagy, pathogens are ubiquitinated and delivered to LC3 + vacuoles via autophagy receptors. In LAP, engagement of PRRs triggers recruitment of Rubicon to LAPosome for degradation. Autophagy pathways function in the removal of pathogens, but also in the control of immune response. Abstract : While classically considered a survival mechanism employed during nutrient scarcity, the autophagy pathway operates in multiple scenarios wherein a return to homeostasis or degradative removal of an invader is required. Now recognized as a pathway with vast immunoregulatory power, autophagy can no longer serve as a 'one size fits all' term, as its machinery can be recruited to different pathogens, at different times, with different outcomes. Both canonical autophagy and the molecularly related, yet divergent pathways non-canonical autophagy are key players in proper host defense and allow us an opportunity to tailor infectious disease intervention and treatment to its specific pathway.